Slow magic: agricultural R&D a century after Mendel - Pardey, Philip G.; Beintema, Nienke M. (2002)
This report assembles and assesses new evidence regarding investments in agricultural R&D, tracking global trends over the past several decades, and highlighting the critical importance that the accumulated stock of scientific knowledge has for today s productivity and for future innovations and economic growth.